Unlocking Flavor Potential of Cheese Balls Enriched with Ipomoea batatas var. Cilembu Assessed by Quantitative Descriptive Sensory Analysis - Brahmanti, Ajeng Astrini; Raditya, Al Raihan Katon (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2025)
The increasing demand for healthier and functional food products has driven innovations in snack development using nutrient-rich local ingredients. This study aimed to develop Potablu Cheese Ball by substituting potato with Cilembu sweet potato and evaluating its sensory characteristics. Three formulations with different potato-to-sweet potato ratios (75:25, 50:50, and 25:75) were prepared. Sensory evaluation was conducted using hedonic and descriptive tests involving 30 semi-trained panelists assessing aroma, color, taste, and texture. The 25:75 formulation (Sample 926) received the highest scores in aroma (4.1) and flavor (4.4), showing strong consumer preference. Descriptive analysis confirmed the dominance of sweet aroma and flavor from Cilembu sweet potato. The findings indicate that incorporating Cilembu sweet potato enhances sensory quality and provides additional nutritional benefits. This product innovation highlights the potential of underutilized local commodities in developing functional, appealing snacks that align with consumer trends toward healthier diets. Contribution to Sustainable Development Goals (SDGs):SDG 2: Zero HungerSDG 3: Good Health and Well-being SDG 12: Responsible Consumption and Production